Analysis of factors affecting gold price in the world market in the 21st century under uncertain circumstances. - Sukkhammee, Kittikhom; Cheenaphet, Supannee (Business Administration and Economics Review, 2023)
Gold was precious in ancient times for religious ceremonies. That currently applies to international reserves and investments. But over the past two decades, gold prices have fluctuated. The study aims to analyze factors affecting gold prices and the long-term equilibrium relationship of gold prices together with the essential economic variables of the US, including the USD, policy interest rate, bond yield, consumer price index, Nasdaq stock indexes, and crude oil prices. The methods of this study used the VAR model with modern econometric tools developed from traditional methods, which are 1) unit root test. 2) long-term equilibrium relationship by cointegration test. 3) test for a cause-effect relationship between variables by causality. 4) analyze impulse-response function, and 5) analyze variance decomposition, using 252 monthly time series data from 2001-2021. The results show that: 1) Gold prices have a long-term equilibrium relationship with the USD, policy interest rate, bond yield, consumer price index, Nasdaq stock indexes, and crude oil prices by cointegration test. 2) USD and inflation are the main that affects the gold price. When the USD strengthens, the gold price will decrease. As inflation increases, gold prices increase by causality test. 3) The shock of bond yields has an influence the greatest on gold price volatility by impulse-response function and variance decomposition test.